Psychosocial Adjustment and Sociometric Status in Primary Education: Gender Differences - Muñoz-Silva, Alicia; De la Corte de la Corte, Cecilia; Lorence-Lara, Bárbara; Sanchez-Garcia, Manuel (Frontiers in Psychology, 2020)
The acceptance or rejection of classmates is one of the most widely recognized determinants of wellbeing in childhood. This study analyses psychosocial adjustment and sociometric status in primary education pupils, and possible differences by gender. A cross-sectional survey was undertaken in Huelva (Spain). The surveyed schools were selected using a stratified random sampling technique with both public and private elementary schools. Sample was composed of 247 4th grade students. Data revealed gender differences in psychosocial adjustment, particularly in terms of prosocial behavior in girls and behavioral problems in boys. Popular and rejected statuses presented opposing adjustment profiles, particularly in hyperactive symptoms and behavioral problems. When the sample was separated by gender, the differences between the types of status in emotional symptomatology and prosocial behavior disappeared. In addition, the differences between statuses were greater in boys, and were defined mainly by hyperactivity, whilst for girls these differences were more apparent in behavioral problems. This study provides support for the existence of a relationship between psychosocial adjustment and sociometric status in childhood and highlights the unique support needs of boys and girls that show antisocial behavior, particularly those with hyperactive symptomatology.